Fluktuasi Harga Ubi Kayu dan Kesejahteraan Petani dalam Perspektif Ekonomi Syariah - Salsabila Murjarisa; Syamsul Hilal; Is Susanto (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Cassava is one of the leading commodities of Lampung Province which is the main source of income for farmers in Tulang Bawang Barat Regency, but the selling price often experiences sharp fluctuations due to the cutting system (rafaksi) and the determination of shaft levels that are not transparent, so that it has an impact on the uncertainty of income and welfare of farmers. This study aims to analyze the conditions of cassava price fluctuations, its effect on farmers' welfare, and examine them based on the principles of justice (al-'adl), benefits (maslahah), and welfare (falah) from the perspective of sharia economics. The study used mixed methods with a sequential explanatory design, which combined a simple regression analysis of 68 farmer respondents with in-depth interviews with farmers, intermediary traders, agricultural extension workers, and religious leaders. The results showed that cassava price fluctuations had a negative and significant effect on farmers' welfare, with a regression coefficient of -1.110 and a significance of 0.000 (<0.05), as well as the ability to explain welfare variation of 41.9% (R² = 0.419). Qualitatively, it was found that the practice of pricing in the field did not fully reflect the principles of Islamic muamalah, characterized by the weak bargaining position of farmers (contrary to the principle of taradhin), the lack of transparency of the crop deduction system (contrary to the principle of al-ablution), and the practice of wholesale buying and selling that had the potential to contain elements of gharar and tadlis. This study concludes that it is necessary to strengthen the market supervision function (hisbah) by local governments in order to realize transparency, justice, and benefits for cassava farmers in a sustainable manner